The Challenge of Globalization for Indian Universities - Naik, B. M. (Journal of Engineering Education Transformations, 2000)
Indian Universities by world standards are far too behind their counterparts in developed countries. They operate still on old lines as if they are an extension of high school system. whereas, Universities in developed countries like U.S.A., Germany, U.K. are primarily research Universities.